Completeness and correctness of cholecystectomy data in a national register—gallriks. (December 2014) - Rystedt, J.; Montgomery, A.; Persson, G.
Background and Aims: To validate the Swedish Register for Gallstone Surgery and Endoscopic Retrograde Cholangiopancreatography (GallRiks) concerning completeness and correctness of entered data for cholecystectomies and evaluating the effect of repeated audits. It is crucial for any register to obtain a high accuracy in order to be a credible and reliable source for quality evaluation, research, and development. Materials and Methods: Completeness was determined by cross-matching the register with the Swedish National Patient Register. Completeness and overall correctness were assessed by comparing registered data to medical records. Correctness for rare occasions, such as bile duct injuries, was evaluated by comparing with claims sent to the Swedish Patient Insurance. Results: Of 64, 538 cholecystectomies, 82.9% of the operations were registered in GallRiks and the coverage increased over time. By random sample, 94, 919 sets of data were available for comparison at the first and second audit and the entries were found to be correct in 97.2% and 98.2% cases, respectively. A 100% correctness for bile duct injuries ( n = 40) was seen when the index-operation was registered in GallRiks. Conclusion: GallRiks demonstrates high completeness, high correctness of entered data, and no indications of failure to report serious adverse events. Repeated audits increased the quality of registered data. GallRiks may be used for clinical evaluation on local and national level and the database enables scientific studies to be performed.